Społeczny odbiór Solidarnej Polski Zbigniewa Ziobry - Marmola, Maciej; Olszanecka, Agata (Political Preferences, 2013)
This article is an attempt to describe the social reception of United Poland (Solidarna Polska) - the new party on Polish political scene founded by former Minister of Justice Zbigniew Ziobro. The authors have tried to answer the question whether this new political initiative can reach the relevant position in Polish party system. The first part of article includes the most popular theoretical models referring to emergence of new political parties and their impact on party system. The other part presents the main issues connected with United Poland: the genesis of this party, the political program and the marketing strategy. It has been an introduction to show the results of our research on the social reception of United Poland. According to the research, only a small number of voters believe in success this new party. The most of Polish electorate think that United Poland cannot develop the coherent marketing strategy and their political program cannot be distinguished from parties with parliamentary representation.